Design of Cooperative Learning Module Elements to Improve Indonesian Vocabulary of Early Childhood - Juni Atma, Ratin Wahyu; Bacotang, Juppri; Mustafa, Mazlina Che; Hafizi, M Zainul; Ismi, Lailatul (Universitas Tanjungpura, 2024)
The low ability of young children in Indonesian vocabulary requires appropriate learning techniques. Cooperative learning is appropriate learning used to teach vocabulary in early childhood. The purpose of the research was to determine the expert's assessment of the activity elements in the cooperative learning module to improve the vocabulary of Indonesian language in early childhood. The research sample consisted of 15 teachers and lecturers in the field of early childhood education who were selected based on purposive sampling. In this study, the Fuzzy Delphi Method (FDM) using five Likert scales was used to collect expert assessment data. Data were analyzed using Triangular Fuzzy Numbers and Defuzzification Process. In this research, the Fuzzy Delphi Method (FDM) using five Likert scales was used to collect expert assessment data. Data were analyzed using Triangular Fuzzy Numbers and Defuzzification Process. The results showed that 13 elements of the learning module activities had met expert agreement or had been accepted by experts. In conclusion, this research has succeeded in developing the design of cooperative learning module elements to improve early childhood vocabulary that is systematic and in accordance with the curriculum. The implications of this research can be used as a guide for developing modules and improving learning.